2009
DOI: 10.1097/cad.0b013e32832a2cd4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of GSTπ expression by tryptanthrin contributing to sensitization of doxorubicin-resistant MCF-7 cells through c-jun NH2-terminal kinase-mediated apoptosis

Abstract: Overexpression of GSTpi and underexpression of Topo II expression are associated with multidrug resistance (MDR) phenotype through nontransporter pathway. Tryptanthrin, a quinazoline derivative, was reported to sensitize resistant cells to doxorubicin by downregulation of MDR1 expression. This study aims to extendedly investigate the effect of tryptanthrin on the role of nontransporter-based genes in determining the MDR response in doxorubicin-resistant MCF-7 cells (MCF-7/adr). Results show that tryptanthrin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…We found that GST-π was apparently over-expressed in the MCF-7/TAX cell line which was associated with paclitaxel resistance, simultaneously, in in-vivo experiment, the expression of GST-π was also upregulated in tumor tissues of MDR nude mice model, these demonstrated that the paclitaxelinduced MDR was mediated by GST-π. In adriamycin resistant human myelogenous leukemia (K562/A02) cells and MCF-7 cells (MCF-7/adr), the MDR was both modulated by the alteration of GST-π and activity of GSTrelated enzymes as well (Yu et al, 2009;Song et al, 2011). In brief, it illustrated that the overexpression of GST-π was related to MDR in breast tumors and indicated poor prognosis to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that GST-π was apparently over-expressed in the MCF-7/TAX cell line which was associated with paclitaxel resistance, simultaneously, in in-vivo experiment, the expression of GST-π was also upregulated in tumor tissues of MDR nude mice model, these demonstrated that the paclitaxelinduced MDR was mediated by GST-π. In adriamycin resistant human myelogenous leukemia (K562/A02) cells and MCF-7 cells (MCF-7/adr), the MDR was both modulated by the alteration of GST-π and activity of GSTrelated enzymes as well (Yu et al, 2009;Song et al, 2011). In brief, it illustrated that the overexpression of GST-π was related to MDR in breast tumors and indicated poor prognosis to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the apoptotic markers, cleaved caspase-3 and cleaved PARP, [30] were monitored by Western blot analysis of HCT15 cells treat- Tryptanthrin was reported to have MDR-reversing effects through down-regulation of the MDR1 gene expression and protein synthesis. [31][32][33] Benzo[b]tryptanthrin has one more benzene ring attached to tryptanthrin (Figure 1). According to the previously reported results, benzo-annulation did not change the topo I inhibition activity, but noticeably enhanced the topo II inhibitory activity and cytotoxicity against HCT15 cells.…”
Section: Benzo[b]tryptanthrin Potentially Binds To the Atp-binding Pomentioning
confidence: 98%
“…Tryptanthrin is a phytochemical found in the medicinal indigo plants such as Polygonum tinctorium and Isatis tinctoria. It was found to possess a wide spectrum of biological and pharmacological activities, including anti-microbial (7-9), immunomodulatory (11-13), antiinflammatory (13-15) and anti-tumor (16)(17)(18)(19) activities. A previous report has shown that tryptanthrin is able to induce both apoptosis and differentiation in the human leukemia HL-60 cells and U-937 cells in vitro (16), however, the underlying action mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Reaction mixture containing 40 units of RN ASE OUT TM recombinant ribonuclease inhibitor, 1 M-MLV first strand buffer, 0.5 mM of each dNTP, 10 mM DTT, 0.1g oligo (dT) [12][13][14][15][16][17][18] and 200 units of M-MLV reverse transcriptase was prepared, and 2 g RNA sample was added into 20 l reaction mixture. A negative control using DEPCtreated water instead of RNA sample was used to check if there was any contamination.…”
Section: Reverse Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation